Persistent Motor Deficits in DAMP - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Motor control in ability to perform everyday and spare-time activities was assessed at 11 to 12 years of age in 10 boys with deficits in attention, motor control and perception (DAMP) and compared with a group of 20 boys without DAMP.